Exogenous testosterone in women enhances and inhibits competitive decision-making depending on victory–defeat experience and trait dominance. (October 2015) - Mehta, Pranjal H.; Son, Veerle van; Welker, Keith M.; Prasad, Smrithi; Sanfey, Alan G.; Smidts, Ale; Roelofs, Karin
Highlights: Testosterone had a causal impact on human competitive decision-making. Testosterone increased competitive decisions after victory in high-dominant individuals. Testosterone reduced competitive decisions after defeat in all participants. Testosterone's behavioral effects were similar across opponent ranks. Testosterone's influence on behavior depends on context and personality. Abstract: The present experiment tested the causal impact of testosterone on human competitive decision-making. According to prevailing theories about testosterone's role in social behavior, testosterone should directly boost competitive decisions. But recent correlational evidence suggests that testosterone's behavioral effects may depend on specific aspects of the context and person relevant to social status (win–lose context and trait dominance). We tested the causal influence of testosterone on competitive decisions by combining hormone administration with measures of trait dominance and a newly developed social competition task in which the victory–defeat context was experimentally manipulated, in a sample of 54 female participants. Consistent with the hypothesis that testosterone has context- and person-dependent effects on competitive behavior, testosterone increased competitive decisions after victory only among high-dominant individuals but testosterone decreased competitive decisions after defeat across all participants. These results suggest that testosterone flexibly modulates competitive decision-making depending on prior social experience and dominance motivation in the service of enhancing social status.